Refining of water masses at Sarawak waters, Malaysia - Ann Aletheia Manson; Aazani Mujahid; Ejria Saleh; Liew, Ju Neng (Borneo Marine Research Institute, 2024)
Water mass identification is essential to understand the dynamics of water circulation. The waters off Sarawak are influenced by the northeast and the southwest monsoons. We studied the physical oceanography of the South China Sea along these waters, from data collected during the Prime Marine Scientific Expedition 2009. The expedition was organized by the Malaysian Ministry of Science, Technology, and Innovation through the National Oceanography Directorate. The physical properties of seawater were obtained using the 'Conductivity-Temperature-Depth' (CTD) profiler from the ocean surface to a water depth of 523 meters. Measurements were recorded from 62 stations, with the furthest offshore distance being approximately 471 kilometers from the nearest point of Sarawak's mainland. The aim of this study is to identify the mass features of Sarawak waters. We employed the T-S diagram and refined the water masses based on previous studies conducted in the South China Sea. The constructed vertical salinity and temperature profiles showed that salinity increases towards the sea bottom, whereas temperature decreases as water depth increases. Five water masses were identified off Sarawak waters, namely Continental Shelf Water (CSW), Open Sea Water (OSW), Maximum Salinity Water (MSW), Permanent Thermocline Water (PTW), and Water Mass 1 (WM1). WM1 is derived from the mix of OSW and MSW masses. Results of this study are useful for studies in primary productivity and the distribution of marine resources in these waters.